2019
DOI: 10.4049/jimmunol.1900046
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antibiotic Therapy Reduces Circulating Inflammatory Dendritic Cells and Treg–Th17 Plasticity in Periodontitis

Abstract: Periodontitis (PD) is a common dysbiotic inflammatory disease that leads to local bone deterioration and tooth loss. PD patients experience low-grade bacteremias with oral microbes implicated in the risk of heart disease, cancer, and kidney failure. Although Th17 effectors are vital to fighting infection, functional imbalance of Th17 effectors and regulatory T cells (Tregs) promote inflammatory diseases. In this study, we investigated, in a small pilot randomized clinical trial, whether expansion of inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 85 publications
0
41
0
3
Order By: Relevance
“…The microbiome likely plays a role in Treg transdifferentiation, as various Clostridium species of human origin favor the induction of murine colonic Foxp3 + Treg cells co-expressing RORγt (55). At least one study has demonstrated that antibiotic treatment that reduces levels of periodontal pathogens reduces the number of IL-17 + Foxp3 + T cells from peripheral blood of periodontitis patients, again supporting a connection between inflammatory environment, microbiome, and Treg plasticity (87).…”
Section: Transdifferentiation Of Foxp3 Cre Fate-tracked Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…The microbiome likely plays a role in Treg transdifferentiation, as various Clostridium species of human origin favor the induction of murine colonic Foxp3 + Treg cells co-expressing RORγt (55). At least one study has demonstrated that antibiotic treatment that reduces levels of periodontal pathogens reduces the number of IL-17 + Foxp3 + T cells from peripheral blood of periodontitis patients, again supporting a connection between inflammatory environment, microbiome, and Treg plasticity (87).…”
Section: Transdifferentiation Of Foxp3 Cre Fate-tracked Cellsmentioning
confidence: 95%
“…Populations of Foxp3 + RORγt + cells with Th17 potential have been reported in human peripheral blood (86). These double positive cells were found to have significantly lower expression of Foxp3 than classical suppressive Tregs, although other groups have reported that human pro-inflammatory IL-17A + Foxp3 + T cells have significantly higher expression of Foxp3 than classic Tregs (87). Suppressor Foxp3 int.…”
Section: Transdifferentiation Of Foxp3 Cre Fate-tracked Cellsmentioning
confidence: 99%
“…However, although the autoantibody profile against citrullinated peptides remained unaffected, it was shown in another uncontrolled study that FMD plus antibiotics could be beneficial for RA in some highly selected patients (154). More mechanistically, no significant changes in the peripheral blood DC or T cell population were observed upon standard nonsurgical local therapy for PD (136), but myeloid DCs (mDCs) with a pro-inflammatory phenotype were reduced upon one week of antibiotic co-therapy (136). These changes in numbers of mDCs with an inflammatory phenotype to the levels of healthy control subjects was paralleled by lower Th17 to Treg ratios (136).…”
Section: Effects Of Pd Treatment On Ramentioning
confidence: 99%
“…DCs can be subdivided into predominantly resident DCs and those with migratory potential. For the spreading of RA relevant antigens, the latter appear to be of greater interest (136). With regard to their migratory capacity, Pg.…”
Section: Switching From Innate To Adaptive Immunitymentioning
confidence: 99%
“…erefore, the plasticity and cross-talk in T-cell subsets are vital for the regulation of the cellular immune response during periodontitis and therapeutic strategies comprising Tregs inhibiting the immuno-inflammatory response and restoring alveolar bone homeostasis [55]. Indeed, the effect of antibiotic therapy in regulating Treg-17 plasticity in humans with periodontitis is demonstrated [56].…”
Section: T Cells In Cellular Immunementioning
confidence: 99%